Plano de comunicação para o Chatbot Bel: ressignificação de saberes e práticas em Relações Públicas no apoio a um Projeto de Extensão à mulher vítima de violência - Oliveira, Natalia Campos de [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The study aims to present a communication plan for the dissemination of a virtual assistant (Chatbot) for guidance on reports of violence against women, in addition to bringing a discussion about the performance of public relations as an agent of public communication focused on building citizenship, marking itself on the right to information to combat gender inequality, regarding the promotion of life free of violence and discrimination. It also brings in its report the extension activity in the process of training of public relations, which faces a gap between education and social reality, whose overcoming is through openness, participation and contact with communities in their daily lives. The methodology used was participant observation, because as a volunteer in the project "Faces of Information and Communication in Health: care for women in situations of violence in Bauru-SP" of Unesp, it was possible to participate in the strategies undertaken in the year 2021, especially about the construction and content modeling of the chatbot, in order to be able to draft a plan for its dissemination to the community. In addition, bibliographical research on public communication and its fundamental importance in promoting the right to information for women was carried out. As a result, besides the experience of acting in the Project, which generated more knowledge about the subject, a look at the problems faced by victims of violence and the intellectual maturation about the making of public relations in the social sphere, brought the awareness that effective communication, via chatbot, can ensure that women can participate actively in the process of confronting this problem, reporting, bringing demands and monitoring the policies that can combat it.

O estudo tem o objetivo de apresentar um plano de comunicação para a divulgação de um assistente virtual (Chatbot) de orientação sobre denúncias de violência à mulher, além de trazer uma discussão sobre a atuação das relações públicas como agente da comunicação pública focada na construção da cidadania, demarcando-se no direito a informação para o combate à desigualdade de gênero, no que tange à promoção da vida livre de violência e de discriminação. Traz ainda em seu relato a atividade de extensão no processo de formação do relações-públicas, que enfrenta uma defasagem entre o ensino e a realidade social, cuja superação passa pela abertura, participação e contato com as comunidades em seus cotidianos. A metodologia utilizada foi a observação participante, pois como voluntária do projeto “Faces da Informação e Comunicação em Saúde: atendimento à mulher em situação de violência em Bauru-SP” da Unesp, foi possível participar das estratégias empreendidas no ano de 2021, especialmente sobre a construção e modelagem de conteúdo do chatbot, de modo a conseguir esboçar um Plano para sua divulgação junto à comunidade. Afora isso, realizou-se pesquisa bibliográfica sobre a comunicação pública e sua importância fundamental na promoção do direito à informação para mulheres. Como resultado, além da experiência de atuar no Projeto, o qual gerou maior conhecimento sobre o assunto, um olhar sobre os problemas enfrentados pelas vítimas de violência e o amadurecimento intelectual sobre o fazer do relações-públicas no âmbito social, trouxe a conscientização de que a comunicação eficaz, via chatbot, pode assegurar que as mulheres possam participar de forma ativa no processo de enfrentamento desta problemática, denunciando, trazendo as demandas e acompanhando as políticas que podem combatê-la.
Communication plan for Chatbot Bel: resignification of knowledge and practices in Public Relations in support of an Extension Project for women in violence
Keywords: Chatbot; Public relations; Crime against women; Communication; Relações públicas; Crime contra as mulheres; Comunicação